USM WON PART 1 & PART 2 CATEGORIES IN PAM-ZSR ARCHITECTURE PRIZE 2016 - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
PENANG, 4 April 2017 - For the second time, Pertubuhan Arkitek Malaysia (PAM), in collaboration with ZSR Architecture Ventures Sdn.Bhd as the prize benefactor, has again organized the prestigious PAMZSR Architecture Prize 2016 that aims to recognize the best designs from the top architecture students of the various Lembaga Arkitek Malaysia (LAM) accredited universities in Malaysia, for both LAM Part 1 and 2 categories.